Macaulay : the tragedy of power - Sullivan, Robert E., 1947- (The Belknap Press of Harvard University Press, 2009)
On the 150th anniversary of the death of the English historian and politician Thomas Babington Macaulay, Robert Sullivan offers a portrait of a Victorian life that probes the cost of power, the practice of empire, and the impact of ideas. Devoting his huge talents to gaining power -- above all for England and its empire -- made Macaulay's life a tragedy. Sullivan offers an unsurpassed study of an afflicted genius and a thoughtful meditation on the modern ethics of power.